To kill a mockingbird (New York : Warner Books, 1982)
The explosion of racial hate in an Alabama town is viewed by a little girl whose father defends a black man accused of rape.
Keywords: Fathers and daughters -- Fiction; Race relations -- Fiction; Trials (Rape) -- Fiction; Girls -- Fiction; Southern States -- Fiction; Domestic fiction; Bildungsromans; Legal fiction (Literature).